Detection of hepatitis C virus core protein in serum by atomic force microscopy combined with mass spectrometry - Ivanov YD (Dove Medical Press, 2015)
Yuri D Ivanov,1 Anna L Kaysheva,1,2 Pavel A Frantsuzov,1 Tatyana O Pleshakova,1 Nikolay V Krohin,1 Alexander A Izotov,1 Ivan D Shumov,1 Vasiliy F Uchaikin,1 Vladimir A Konev,1 Vadim S Ziborov,1 Alexander I Archakov11Institute of Biomedical Chemistry, 2PostgenTech Ltd, Moscow, RussiaAbstract: A method for detection and identification of core antigen of hepatitis C virus (HCVcoreAg)-containing particles in the serum was proposed, with due account taken of the interactions of proteotypic peptides with Na+, K+, and Cl- ions. The method is based on a combination of reversible biospecific atomic force microscopy (AFM)-fishing and mass spectrometry (MS). AFM-fishing enables concentration, detection, and counting of protein complexes captured on the AFM chip surface, with their subsequent MS identification. Biospecific AFM-fishing of HCVcoreAg-containing particles from serum samples was carried out using AFM chips with immobilized antibodies against HCVcoreAg (HCVcoreAgim). Formation of complexes between anti-HCVcoreAgim and HCVcoreAg-containing particles on the AFM chip surface during the fishing process was demonstrated. These complexes were registered and counted by AFM. Further MS analysis allowed reliable identification of HCVcoreAg within the complexes formed on the AFM chip surface. It was shown that MS data processing, with account taken of the interactions between HCVcoreAg peptides and Na+, K+ cations, and Cl- anions, allows an increase in the number of peptides identified.Keywords: hepatitis C virus, molecular detector, biospecific fishing